Analisis Karakteristik Curah Hujan di Pulau Kalimantan dan Hubungannya pada Fase El-Niño dan IOD Positif - Putri Maulida, Nabila; Ariska, Melly; Suhadi, Suhadi; Akhsan, Hamdi (Jurusan Fisika FMIPA Universitas Andalas, 2025)
This study aims to analyze the characteristics of rainfall in Kalimantan Island during the ENSO and IOD phases using composite method. This study uses ERA5 reanalysis data for the period 1985-2023. The analysis was carried out using Python in Jupyter Notebook Software to visualize rainfall patterns across four seasons (DJF, MAM, JJA, and SON). The results indicate that El Niño events reduce rainfall during the JJA season, with the largest deficit occurring in the southern region of Kalimantan, where rainfall drops to less than 5 mm per season. Conversely, Positive IOD conditions exacerbate drought, resulting in decreased rainfall in the southern and central parts of the island. The combined effects of El Niño and Positive IOD cause an even more significant decline in rainfall, with the dry season experiencing a substantial reduction compared to normal conditions. This study provides important insights for hydrometeorological risk mitigation in Kalimantan, highlighting the need for adaptive management in response to climate variability.